Embracing Today’s Economic And Technological Reality What It Means For Design Professionals - YASEMIN INCE GUNEY (Journal of Contemporary Urban Affairs, 2018)
History has shown that technological advancements alter the way we produce, exchange, protect, consume and save all kinds of goods. The First Industrial Revolution, for example, has been named as such since it indeed revolutionized everything related to daily living including art, culture, economy and politics. History has also shown that most cultural actors are reluctant to embrace advanced technology at first as they might see it as taking away something at the core of humanity. Arts and Crafts movement, for example, grew out of a concern for the effects of industrialization on design, on traditional skills and on the lives of ordinary people. Today, economists, scientists and policymakers in developing countries are talking about the coming of the fourth industrial revolution and the Second Machine Age, that not only will redefine the way humans live their daily life but also the very definition of human beings. The aim of this study is to discuss the effects of these changes on theoretical and practical issues related to design professionals and education, including advanced technologies available and social and cultural implications of their use. The paper will argue that today’s economic and technological reality will alter the design profession from its education to its implementation.